Digital Literacy of Taxpayers and Its Effect on Compliance with Annual Tax Return (SPT) Reporting in Indonesia - Rhea Silva Aliifah; Ana Farida Sahara; Yananto Mihadi Putra (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
This study aims to examine the effect of digital literacy on taxpayer compliance in electronically submitting the Annual Tax Return (SPT). The digital transformation of the tax system by the Directorate General of Taxes, through platforms like e-Filling and DJP Online, requires taxpayers to possess adequate digital skills. This research uses a literature review method , analyzing national and international studies published between 2021-2025. The findings show that digital literacy significantly contributes to tax reporting compliance. Taxpayers with good digital skills tend to be more compliant and efficient in their reporting process. These findings support the Theory of Planned Behavior, which explains that attitudes, subjective norms, and perceived control over technology influence compliance intention. This research is also relevant to the academic context of Tax Planning and Tax Accounting, as digital literacy underpins effective tax reporting and accurate recording. Therefore, enhancing taxpayers digital literacy is a strategic step toward improving compliance and optimizing digital taxation systems.